Persepsi kepercayaan dalam pemberian Makanan Pendamping ASI dan pencegahan stunting di Kabupaten Banyuasin - Nandira, Terra; Fajar, Nur Alam; Munadi, Muhammad Cholil (Poltekkes Kemenkes Aceh, 2025)
Background: Stunting is a significant health issue in children that impedes their growth and development due to prolonged nutritional deficiencies. Banyuasin Regency in South Sumatra, Indonesia, has a notably high prevalence of Stunting, reaching 24.8%. This problem is influenced by socio-cultural factors, including maternal perceptions and beliefs regarding the provision of complementary foods for breast milk.Objectives: The objective of this study is to examine the association between maternal perceptions and beliefs about Complementary Feeding Practices and Stunting prevention in Banyuasin Regency.Methods: The sampling procedure employed a purposive sampling approach, yielding a sample size of 106 respondents. The inclusion criteria consisted of mothers with children between the ages of 6 and 24 months residing in Banyuasin Regency. Data collection was facilitated through the use of a questionnaire. The analytical approach involved univariate analysis to provide a general description of each variable, and bivariate analysis was conducted using the Chi-Square test to examine the relationships between variables.Results: The results of the study show whether maternal perceptions are significantly related to maternal actions in providing Complementary Feeding for Stunting prevention.Conclusion: The findings of this study indicate that maternal perceptions of vulnerability, severity, and benefits are significantly associated with their actions in providing Complementary Feeding and the occurrence of Stunting. Conversely, perceptions of barriers do not demonstrate a statistically significant relationship.